Spatiotemporal imaging of plasmonic fields near nanoparticles below the diffraction limit - Saydanzad, Erfan; Li, Jianxiong; Thumm, Uwe (My University, 2018)
Optically induced collective conduction-electron oscillations can generate intense plasmonic fields near metallic nanoparticles. We suggest a method for reconstructing such nanoplasmonic fields with nanometer spatial and sub-femtosecond temporal resolution from streaked photoemission spectra. Applying this imaging scheme to Au nanospheres, we demonstrate the accurate spatiotemporal reconstruction of the plasmonic near-field distribution in comparison with the directly calculated plasmonic field.